2005
DOI: 10.1088/0963-0252/14/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Design and preliminary characterization of a miniature pulsed RF APGD torch with downstream injection of the source of reactive species

Abstract: The design of a miniature low-power atmospheric pressure glow discharge torch (APGD-t) and the results of its preliminary electrical and spectroscopic characterization are presented. A capacitively-coupled pulsed RF (13.56 MHz) helium plasma jet is formed in a converging confinement tube and O 2 is injected downstream in the plasma afterglow region through a capillary electrode. With 1 SLM He, the APGD-t produced a non-thermal plasma jet of 500 µm-diameter and ≈2.5 mm-long at power levels ranging from 1 to 5 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
126
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 37 publications
6
126
0
Order By: Relevance
“…It is worth mentioning that UV emission was found to be similarly weak in other studies of pulsed APGD jets. 10,13 This suggests that the APGD jets considered in this study are likely to enable applications through their reactive plasma species. Interestingly, optical emission intensities of the pulsed APGD jet were greater even though its power consumption was lower.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…It is worth mentioning that UV emission was found to be similarly weak in other studies of pulsed APGD jets. 10,13 This suggests that the APGD jets considered in this study are likely to enable applications through their reactive plasma species. Interestingly, optical emission intensities of the pulsed APGD jet were greater even though its power consumption was lower.…”
mentioning
confidence: 95%
“…[2][3][4][5][6][7][8][9][10][11] The vast majority of APGD jets reported so far employ sinusoidal excitation, although it has been known that nonsinusoidal excitation, through voltage pulsing, for example, offers a useful freedom to further improve APGD performance. 12 Initial results from few reported studies of pulsed APGD jets 4,10,13 have shown their general similarity to and contrast with sinusoidal APGD jets. However, a direct comparison of pulsed and sinusoidal APGD jets remains elusive, thus casting an uncertainty of whether a pulsed APGD jet offers significant advantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the operating cost versus the equipment size usually increases exponentially for plasma systems. While it is possible to operate cold plasma discharges at atmospheric or near-atmospheric pressures [23,24,25], discharge volumes are severely limited and thus not appropriate for large-scale particle functionalization. Recently, PECVD has also been used for the growth of carbon nanotube [26].…”
Section: Plasma-enhanced Cvd (Pecvd)mentioning
confidence: 99%
“…We recently developed a miniature RF (13.56 MHz) atmospheric pressure glow discharge plasma torch, the so-called APGD-t, whose characteristics are well suited for biomedical applications [12,13]. In the present article, we report on the main characteristics of the APGD-t, on the optimization of the O 2 /He ratio for the maximum production of O radicals, and preliminary experiments on cell detachment and removal.…”
Section: Introductionmentioning
confidence: 99%